2004
DOI: 10.1007/s00276-004-0267-6
|View full text |Cite
|
Sign up to set email alerts
|

A possible etiology of the internal derangement of the temporomandibular joint based on the MRI observations of the lateral pterygoid muscle

Abstract: The purpose of this study was to evaluate the relationship of the temporomandibular joint (TMJ) internal derangement and lateral pterygoid muscle (LPM) by magnetic resonance imaging (MRI). In this study, 115 subjects with TMJ internal derangement (total 230 TMJs) and 21 subjects without clinical symptoms (total 42 TMJs) were included. TMJ disc position and LPM were evaluated using MRI. LPM attachments were categorized into two different types: type 1, where fibers of the superior head of the LPM (SLPM) were at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
3
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 21 publications
5
54
3
7
Order By: Relevance
“…In contrast to our results, Taskaya-Yilmaz et al 10 and Omami et al 7 found only two heads of the LPM. However, their studies were based on samples smaller than that in our investigation, which may explain the different outcomes.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In contrast to our results, Taskaya-Yilmaz et al 10 and Omami et al 7 found only two heads of the LPM. However, their studies were based on samples smaller than that in our investigation, which may explain the different outcomes.…”
Section: Discussioncontrasting
confidence: 56%
“…This finding stands in contrast to most of the studies investigating this relationship. Omami et al, 7 Taskaya-Yilmaz et al, 10 Imanimoghaddam et al 6 and Dergin et al 5 did not find a statistically significant relationship between these variables. This discrepancy can partly be explained by the fact that our study group was larger and that we used a different methodology for disc assessment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The decrease in size of the condyle increases joint space and thereby reduces pain. Taskaya et al [4 ], in a magnetic resonance imaging (MRI) study of 115 patients with TMJ ID and 21 subjects without clinical symptoms, found that spasm of lateral pterygoid muscle causes disc displacement and atrophy following degeneration of the lateral pterygoid muscle. A case of closed lock surgically corrected by performing eminectomy is being presented.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 There has been extensive investigation of the anatomic relationship of the LPM to the condylar head, disk, and capsule, as well as multiple electromyographic studies that demonstrate the patterns of contraction of the muscles of mastication during both rest and motion. [3][4][5][6][7] Wang et al 3 recently demonstrated maximal activity of the superior head of the lateral pterygoid muscle (SHLP) during clenching, with its major function as a stabilizer of the disk and condylar head.…”
mentioning
confidence: 99%